2022
DOI: 10.3390/su14127499
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Other Vulnerabilities to Water–Energy Accessibility in Rural Households of Katsina State, Northern Nigeria

Abstract: Water and energy are essential resources for all people. However, despite the availability of sufficient water and energy resources, men and women continue to be subject to unequal rights to both water and energy in terms of access, allocation, gathering, and quality of resources. Socio-economic parameters, which include gender, income, and location, are determinant factors of water and cooking energy accessibility in this study. The research aims to assess the accessibility of water and cooking fuels across f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…In the conversion cost, only the construction fee, maintenance fee, and agricultural irrigation risk compensation fee for water-saving projects are calculated, and the conversion price for water rights is calculated at 0.297 CNY/m 3 . The government did not consider the cost of water-saving projects during the pricing process, as well as the compensation of farmers as water users, so the water rights conversion costs and prices were underestimated and did not fully reflect the benefits of farmers' water rights and economic losses [36]. That is contrary to the goal of water rights transfer.…”
Section: Comparative Analysismentioning
confidence: 99%
“…In the conversion cost, only the construction fee, maintenance fee, and agricultural irrigation risk compensation fee for water-saving projects are calculated, and the conversion price for water rights is calculated at 0.297 CNY/m 3 . The government did not consider the cost of water-saving projects during the pricing process, as well as the compensation of farmers as water users, so the water rights conversion costs and prices were underestimated and did not fully reflect the benefits of farmers' water rights and economic losses [36]. That is contrary to the goal of water rights transfer.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Interactions among these nexus components play a vital role in the living standard outcomes of marginalized households, and can be captured and/or affected through changes in household behaviors or activities (Villamor et al, 2018). Access to, control over, and the use of WELF resources are also influenced by gender, however, not many studies have taken this into consideration nor have they addressed the potential for differential effects of WELF nexus interventions with respect to gender (Villamor et al, 2018;Khadka, 2022;Sani and Scholz, 2022). Women, who constitute two-thirds of the world's poor, are key stakeholders in nexus sectors, however, they face significant structural barriers (Khadka, 2022;Sani and Scholz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Access to, control over, and the use of WELF resources are also influenced by gender, however, not many studies have taken this into consideration nor have they addressed the potential for differential effects of WELF nexus interventions with respect to gender (Villamor et al, 2018;Khadka, 2022;Sani and Scholz, 2022). Women, who constitute two-thirds of the world's poor, are key stakeholders in nexus sectors, however, they face significant structural barriers (Khadka, 2022;Sani and Scholz, 2022). Moreover, the working culture in these sectors is still guided or influenced by masculine attitudes, behaviors, and mindsets and women struggle to access these men-dominated spaces (Khadka, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The scarcity of water resource poses strong potential threats to human survival, especially among the economically disadvantaged rural households. However, the water scarcity involves how the spatially spread societies and their activities are able (or unable) modify the environment with mobilized financial resources and power to shape the patterns of access to water for diverse uses of the resource (Inkani, 2015). This means that the developing countries, with weak public water supply institutions, are at great risk of severe water shortage in the 21st century due to the huge differentials in households' characteristics (Balogun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the appropriate model for measuring the problem is another issue to contend with, in the face numerous indices developed for various scales of measurement (see Table 1.1). Nonetheless, a review of various kinds of literature by Inkani (2015); Nepomilueva (2017); Damkjaek and Taylor (2017) demonstrated that several indices have been developed to assess water scarcity at various scales, as shown in Table 1. Inkani (2015) believed that since domestic water scarcity occurs principally at the household level, the model that utilises household-level data is necessarily needed for the scientific evaluation of the extent of the problem.…”
Section: Introductionmentioning
confidence: 99%